Role of Jalauka Avacharan (Leech Therapy) in the Management of Non-Healing Ulcer: A Case Study - Ankita Negi; Gaurav Parmar; Vivek Thakur (AYUSHDHARA, 2022)
Non-healing ulcers are a serious health issue that affects people all over the world. They are expensive in terms of both human and material resources. Unavoidable and harmful to the lower limb, non-healing ulcers are a leading factor in non-traumatic lower limb amputations. Numerous studies have examined the potential effects of medicinal leech therapy (MLT), also known as hirudotherapy or Jalaukavcharan in Ayurveda on a variety of illnesses, including Skin disorders and inflammatory diseases, as well as various surgical ailments. Despite the lengthy history of complementary health practises, contemporary medicine has only recently focused on their potential mechanisms of action. Many bioactive compounds, including antistasin, eglins, guamerin, hirudin, saratin, and bdellins, as well as complement and carboxypeptidase inhibitors, are secreted by leeches. In addition to extracellular matrix degradative and antibacterial actions, they exhibit analgesic, anti-inflammatory, platelet inhibitory, anticoagulant, and thrombin regulating properties. However, with more research, the range of effects may broaden. The method has been shown to be affordable, efficient, simple to use, and effective. The aim of this study to evaluate the effectiveness of Jalaukavcharan to promote the healing processes in non-healing ulcer. The study was an observational single case design without control group; it was carried out in department of Shalya of Rajiv Gandhi Post Graduate Ayurvedic College, Paprola